Considerations for Improving Metabolism Predictions for In Vitro to In Vivo Extrapolation - Moreau, Marjory; Mallick, Pankajini; Smeltz, Marci; Haider, Saad; Nicolas, Chantel I.; Pendse, Salil N.; Leonard, Jeremy A.; Linakis, Matthew W.; McMullen, Patrick D.; Clewell, Rebecca A.; Clewell, Harvey J.; Yoon, Miyoung (Frontiers in Toxicology, 2022)
High-throughput (HT) in vitro to in vivo extrapolation (IVIVE) is an integral component in new approach method (NAM)-based risk assessment paradigms, for rapidly translating in vitro toxicity assay results into the context of in vivo exposure. When coupled with rapid exposure predictions, HT-IVIVE supports the use of HT in vitro assays for risk-based chemical prioritization. However, the reliability of prioritization based on HT bioactivity data and HT-IVIVE can be limited as the domain of applicability of current HT-IVIVE is limited to intrinsic clearance measured primarily in pharmaceutical compounds. Further, current approaches only consider parent chemical toxicity. These limitations occur because current state-of-the-art HT prediction tools for clearance and metabolite kinetics do not provide reliable data to support HT-IVIVE. This paper discusses current challenges in implementation of IVIVE for prioritization and risk assessment and recommends a path forward for addressing the most pressing needs and expanding the utility of IVIVE.